Interrogating the Anthropocene Ecology, Aesthetics, Pedagogy, and the Future in Question (Palgrave Studies in Educational Futures, 2018)
This volume weaves together a variety of perspectives aimed at confronting a spectrum of ethico-political global challenges arising in the Anthropocene which affect the future of life on planet earth. In this book, the authors offer a multi-faceted approach to address the consequences of its imaginary and projective directions. The chapters span the disciplines of political economy, cybernetics, environmentalism, bio-science, psychoanalysis, bioacoustics, documentary film, installation art, geoperformativity, and glitch aesthetics. The first section attempts to flesh out new aspects of current debates. Questions over the Capitaloscene are explored via conflations of class and climate, revisiting the eco-Marxist analysis of capitalism, and the financial system that thrives on debt. The second section explores the imaginary narratives that raise questions regarding non-human involvement. The third section addresses 'geoartisty,' the counter artistic responses to the speculariztion of climate disasters, questioning eco-documentaries, and what a post-anthropocentric art might look like. The last section addresses the pedagogical response to the Anthropocene. .